Efeito da escovação utilizando dentifrícios com diferentes graus de abrasividade no desgaste do esmalte após o uso de agentes clareadores com e sem cálcio, em diferentes intervalos de tempo - Santos, Luciana Floriani Thives Freitas [UNESP] (2014)
The objective of this study was to evaluate the effects of brushing, using toothpastes with different degrees of abrasiveness after exposure to bleaching agent hydrogen peroxide (HP) 7.5% with or without the addition of calcium gluconate in different time intervals (immediately and after 1 h). The alteration in dental tissue resulting from these interactions on enamel surface wear was analyzed. In this study 144 bovine enamel specimens were divided into 12 groups (n = 12) according to the whitening gel used (with and without calcium), the grade of abrasive (high or low) and the time interval elapsed after use of the bleaching gel (immediately and after 1h). For the control, four groups were not exposed to the bleaching gel and were just submitted to abrasion cycles according to the type of abrasive and the time interval. The bleaching gel was applied for 1 h and after this period, the groups that were brushed immediately were submitted to abrasion cycle, and the ones tested after 1h, remained in artificial saliva before the performance of abrasive cycles. The specimens were subjected to 45 cycles of brushing, corresponding to 3x a day (135 cycles per day - 1 min 30 s). These procedures were repeated for 7 days, totaling 945 cycles at the end of the study. The enamel wear was measured (μm) by profilometry. To check the results, three-way ANOVA and Tukey's test was applied. The significance level was 5%. Statistically significant differences (p =0.0001) for the three tested factors were observed. Mean values (± SD) and results of Tukey test for whitening factor were: NB- 0.45(± 0.01)a, HP+Ca- 0.51(± 0.03)b, HP - 0.82(± 0.01)c. For the abrasive factor were: Low- 0.44(± 0.01)a and High- 0.74(± 0.05)b and for the time interval, were: 1h- 0.41(± 0.01)a, immediately- 0.77(± 0.05) b. It can be concluded that: a) HP 7.5% bleaching increased the enamel susceptibility to abrasion, b) the...